2021
DOI: 10.1093/advances/nmab003
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: The Importance of Water Security for Ensuring Food Security, Good Nutrition, and Well-being

Abstract: Water security is a powerful concept that is still in its early days in the field of nutrition. Given the prevalence and severity of water issues and the many interconnections between water and nutrition, we argue that water security deserves attention commensurate with its importance to human nutrition and health. To this end, we first give a brief introduction to water insecurity and discuss its conceptualization in terms of availability, access, use, and stability. We then lay out the empirical grounding fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 127 publications
0
62
0
Order By: Relevance
“…Moving forward, the measurement of water access and strategies to improve it should be considered when designing integrated interventions. Concurring with Young et al ( 37 ), we propose an interdisciplinary approach to improve water and food security to achieve equity, sustainability, and health at the global level. Based on the review of integrated interventions, we concluded that interventions improving sanitation and hygiene at the household level will be more effective with improved water access and bringing about community-level changes to successfully address the ubiquitous nature of fecal and bacterial contamination of the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving forward, the measurement of water access and strategies to improve it should be considered when designing integrated interventions. Concurring with Young et al ( 37 ), we propose an interdisciplinary approach to improve water and food security to achieve equity, sustainability, and health at the global level. Based on the review of integrated interventions, we concluded that interventions improving sanitation and hygiene at the household level will be more effective with improved water access and bringing about community-level changes to successfully address the ubiquitous nature of fecal and bacterial contamination of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to recognize that water is an essential nutrient, and hence its clean, safe access, and availability, or the “water access” aspect of WASH, can also be counted as a nutrition strategy. In a prospective paper, Young et al ( 37 ) highlighted the importance of accounting for water security in planning food and nutrition programs and policies. It was concluded that consistent availability and access to water should be a goal since they will help to achieve not only SDG no.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] It has also been useful in assessing intervention impacts and advocating for resources. 8 In addition to being a more proximal measure to health and well-being, several additional advantages are gained by shifting the level of analysis from the household to the individual level. For one, individuals are most knowledgeable about their own experiences.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…13 Availability and physical accessibility are necessary but insufficient for water security. 8 14 For example, millions of people cannot reliably access nearby water due to economic, political and/or other barriers. Further, measurements at the regional and community levels can obscure huge inequalities in the distribution of resources.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding water quality, these include organoleptic properties (e.g., taste, smell); (dis)trust in local, regional, and national institutions; knowledge about and familiarity with water management and treatment practices; attitudes toward diverse contaminants; and the beliefs and values of those within an individual's social network 3,20 . Quantifying people's experienced and anticipated harm from drinking water in surveys is also useful because results can be disaggregated to the individual or household level 21 . As such, understanding human experiences with and anticipation of harm from drinking water is critical for designing programs and policies that aim to increase access to and use of safe drinking water.…”
Section: Introductionmentioning
confidence: 99%